2021
DOI: 10.3390/coatings11121445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Harvesting Stages and Calcium Chloride Application on Postharvest Quality of Tomato Fruits

Abstract: Tomatoes are a good source of vitamins, minerals, antioxidants, and enzymes, which are beneficial to human health. They are one of the most commercially high-value vegetable crops that experience a huge postharvest loss after harvest. The present experiment is conducted to investigate the effect of different maturity stages (mature green, breaker, and half-ripe stage), pre- and post-harvest treatment with different concentrations (0.0%, 1.0%, 1.5%, and 2.0%, w/v) of calcium chloride (CaCl2) on the postharvest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
(75 reference statements)
1
10
0
Order By: Relevance
“…Similar results were reported by Dao, Nguyen, Tran, Pham et al. (2021), where a 38% and 55% reduction in TPC and tannin content of cashew apples, respectively, was observed after NaCl‐based‐blanching. Zhou et al.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Similar results were reported by Dao, Nguyen, Tran, Pham et al. (2021), where a 38% and 55% reduction in TPC and tannin content of cashew apples, respectively, was observed after NaCl‐based‐blanching. Zhou et al.…”
Section: Resultssupporting
confidence: 90%
“…Mazumder et al. (2021) studied the effect of CaCl 2 treatment on the preharvest to postharvest maturity stage of tomatoes. They reported that CaCl 2 decreased ethylene production and retained maximum phenolic content after 20 days of storage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the application of calcium chloride after harvest delays the progress of ripening, reduces decay, and increases the calcium level in treated fruits, resulting in higher nutritional value in treated fruits [ 21 , 22 ]. Reducing respiration, ripening development, and senescence were the effects observed in some fruits and vegetables from CaCl 2 application after harvest [ 23 , 24 ]. Moreover, Aghdam et al [ 25 ] found that antioxidant capacity, anthocyanin, ascorbic acid, and phenolic compounds were conserved in cornelian cherry fruits by the postharvest application of CaCl 2 .…”
Section: Introductionmentioning
confidence: 99%